Electrochemical synthesis of corrosion protective polyaniline coatings on mild steel from aqueous salicylate medium - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Science and Technology of Advanced Materials, 2006)
Strongly adherent polyaniline coatings were electrochemically synthesized on mild steel from an aqueous salicylate medium. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy. The extent of the corrosion protection offered by polyaniline coatings to mild steel was investigated in aqueous 3% NaCl solution, 0.01 M Na2SO4 Solution and in aqueous solutions of NaCl + Na2SO4 with different concentrations by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies reveal that the corrosion resistance of the polyaniline-coated mild steel is significantly higher and the corrosion rate is considerably lower than that of uncoated steel. (c) 2006 Published by NIMS and Elsevier Ltd.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; polyaniline coatings mild steel

Corrosion protection aspects of electrochemically synthesized poly(o-anisidine-co-o-toluidine) coatings on copper - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Electrochimica Acta, 2007)
The poly(o-anisidine-co-o-toluidine) coatings were synthesized on copper substrates by electrochemical copolymerization of o-anisidine with o-toluidine using sodium salicylate as supporting electrolyte. These coatings were characterized by cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy (NMR) and scanning electron microscopy (SEM). The formation of the copolymer with the mixture of monomers in the aqueous sodium salicylate solution was ascertained by a critical comparison of the results obtained with the polymerization of the individual monomers, o-anisidine and o-toluidine, respectively. The corrosion protection aspects of poly(o-anisidine-co-o-toluidine) coatings to copper was investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of the potentiodynamic polarization measurements and EIS studies showed that the poly(o-anisidine-co-o-toluidine) coatings provided the effective corrosion protection to copper than that of respective homopolymers. The corrosion rate is observed to depend on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: copolymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-anisidine-co-o-toluidine)

Synthesis of poly(aniline-co-o-toluidine) coatings and their corrosion-protection performance on low-carbon steel - Pawar, Pritee; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2007)
Strongly adherent poly(aniline-co-o-toluidine) coatings were synthesized on low-carbon-steel substrates by the electrochemical copolymerization of aniline with o-toluidine with sodium tartrate as the supporting electrolyte. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, and scanning electron microscopy. The formation of the copolymer with the mixture of monomers in the aqueous sodium tartrate solution was ascertained by a critical comparison of the results obtained from the polymerizations of the individual monomers, aniline and o-toluidine. The optical absorption spectrum of the copolymer was drastically different from the spectra of the respective homopolymers, polyaniline and poly(o-toluidine). The extent of the corrosion protection offered by poly(aniline-co-o-toluidine) coatings to low-carbon steel was investigated in aqueous 3% NaCl solutions by open-circuit-potential measurements and a potentiodynamic polarization technique. The results of the potentiodynamic polarization measurements showed that the poly(aniline-co-o-toluidine) coatings provided more effective corrosion protection to low-carbon steel than the respective homo-polymers. The corrosion rate depended on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (c) 2006 Wiley Periodicals, Inc.
Keywords: Coatings; conducting polymers; copolymerization; synthesis